CONCOMITANT OCCURRENCE OF OXIDATIVE STRESS WITH SUSTANON IN MALE RAT - Y.Z. Al-abdaly; E .R. Al-Kennany; E.K. Al-Hamdany (Basrah Journal of Veterinary Research)
The present study was conducted to investigate the effect of androgenic–anabolic steroids Sustanon 20 mg/ kg on oxidative stress. Twenty male rats weredivided into four groups treated for 4 weeks as once weekly treatment. The 1st groupconsidered as control group, the 2nd group injected with sustanon 20 mg/kgintramuscularly, the 3rd group injected with sustanon intramuscularly 20 mg/kg andthen orally dosage of vitamin E 100 mg\kg, and 4th group got orally dosage of vitaminE 100 mg/kg. The results revealed significant decrease in glutathione level in theserum and tissue of brain and liver in sustanon group as compared with control, whilethere is significant increase in malondialdehyde level in the serum of sustanon groupas compared with control The result showed no different between the groups treatedwith sustanon alone and with sustanon and vitamin E.All the pathological changes have been recorded for the sustanon group onlywhile there were no pathological changes for other groups. The gross pathologicalchanges showed congestion of heart and liver in sustanon group.. The microscopicchanges of heart showed vacuolar degeneration of cardiac cells and edema between it.Liver showed necrosis of hepatic cells, infiltration of inflammatory cells. Lungsrevealed pneumonia with thickening of wall of alveoli and bronchioles byinflammatory cells, and emphysema of alveoli. We conclude from this study that sustanon in high dose have an effect onincrease oxidative stress, macroscopic and microscopic pathological changes in heart,liver and lung, and no effect of vitamin E in this study